Research Performance and University–Industry–Government Funding Sources in Taiwan's Technological and Vocational Universities. Issue 3 (2nd July 2016) - Zhou, Wei; Li, Yanling; Hsieh, Chia-Jen; Chang, Ke-Chiun; Kiang, Yen-Jo; Ken, Yun
Abstract : Research funding in Taiwan's technological and vocational universities is mainly sourced from those scientific and technological projects which were assigned by government, industries or other organizations. It plays an important role in influencing innovation activities, development of new knowledge, and advancement of new-generation technologies. As technology dynamics over time, technological and vocational universities have missions to associate with that. To achieve their missions, more funding supports from university/industry/government are demanded. By analyzing data for Taiwan technology and vocational universities, the object of this study is to investigate a series of indices such as number of patents, patent nationality, number of paper publications, category of paper publications, and their funding sources. We also examine whether and how the faculties' age, education level, academic level, and research performance affect the three types of funding sources from governments, industries, and other organizations. The results have indicated that funding sources in Taiwan's technological and vocational universities are closely referred to the number of patents and paper publications, suggesting that the faculties needs to justify their paper publication and patenting strategies accordingly. Moreover, faculties' age, and academic level have played a positive influence on obtaining funding. Policymakers and universities could consider the general distribution and tendency of the three types of research funding investment and give proper incentives to guide their faculties' research interests and achievements.